2017
DOI: 10.1155/2017/1934724
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Treated Active Carbon for Capacitive Deionization of Saline Water

Abstract: The plasma treatment on commercial active carbon (AC) was carried out in a capacitively coupled plasma system using Ar + 10% O 2 at pressure of 4.0 Torr. The RF plasma power ranged from 50 W to 100 W and the processing time was 10 min. The carbon film electrode was fabricated by electrophoretic deposition. Micro-Raman spectroscopy revealed the highly increased disorder of sp 2 C lattice for the AC treated at 75 W. An electrosorption capacity of 6.15 mg/g was recorded for the carbon treated at 75 W in a 0.1 mM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…It was possible to see the reduction and oxidation peaks, which stand for the anodic and catholic electrocatalytic activity. 37 CV analyses of untreated and oxygen plasma-treated ACPSC are carried out using KOH electrolyte. With a reduced scan rate of 10 mV s −1 , untreated ACPSC has a specific capacitance of 620 F g −1 , while utilizing a rapid scanning rate, it falls to 196 F g −1 .…”
Section: Results and Disscusionmentioning
confidence: 99%
“…It was possible to see the reduction and oxidation peaks, which stand for the anodic and catholic electrocatalytic activity. 37 CV analyses of untreated and oxygen plasma-treated ACPSC are carried out using KOH electrolyte. With a reduced scan rate of 10 mV s −1 , untreated ACPSC has a specific capacitance of 620 F g −1 , while utilizing a rapid scanning rate, it falls to 196 F g −1 .…”
Section: Results and Disscusionmentioning
confidence: 99%
“…[35,44,66] However, most researchers have experimented with both parameters under moderate conditions. [38][39]63,67] Optimization of these parameters will pave the way towards the synthesis of a superior AC material that will have a high functional groups content, a high specific surface area, a higher degree of surface porosity, efficient catalytic properties, high capacitance, and enhanced hydrophilic nature. Statistical data of recent studies related to plasma functionalization of AC is summarized in Figure 3.…”
Section: Discharge Process Efficiency and Treatment Timementioning
confidence: 99%
“…It was observed that some researchers have varied treatment time based on the efficiency of the source, i. e. high efficiency‐low treatment time and vice versa [35,44,66] . However, most researchers have experimented with both parameters under moderate conditions [38–39,63,67] . Optimization of these parameters will pave the way towards the synthesis of a superior AC material that will have a high functional groups content, a high specific surface area, a higher degree of surface porosity, efficient catalytic properties, high capacitance, and enhanced hydrophilic nature.…”
Section: Introduction To Plasma Functionalization Of Acmentioning
confidence: 99%